2017
DOI: 10.1089/acu.2017.1232
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Achilles Tendinopathy with Electroacupuncture: Two Cases

Abstract: Achilles tendinopathy is a common injury for active patient populations and is challenging to treat. Acupuncture tendon-based therapy was first described in the . In modern times, specific techniques have been described poorly in the literature. The aim of this case report is to describe a new technique of acupuncture for the treatment of Achilles tendinopathy and provide 2 illustrative cases. Treatments for the 2 patients were performed in a deployed military treatment facility. SERIN® 0.25 mm × 40 mm needles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This result is consistent with other studies that have reported successful pain management as a critical indicator of effective Achilles tendon repair. 22,23 The reported levels of ankle stiffness and calf-muscle weakness in the study also provide valuable information. While a majority of participants experienced no (71.43%) or only mild (28.57%) stiffness and weakness (64.29%) with no weakness, 28.57% with mild weakness, and 7.14% with moderate weakness), these symptoms are not uncommon following Achilles tendon repair.…”
Section: Discussionmentioning
confidence: 97%
“…This result is consistent with other studies that have reported successful pain management as a critical indicator of effective Achilles tendon repair. 22,23 The reported levels of ankle stiffness and calf-muscle weakness in the study also provide valuable information. While a majority of participants experienced no (71.43%) or only mild (28.57%) stiffness and weakness (64.29%) with no weakness, 28.57% with mild weakness, and 7.14% with moderate weakness), these symptoms are not uncommon following Achilles tendon repair.…”
Section: Discussionmentioning
confidence: 97%